2015
DOI: 10.1155/2015/278287
|View full text |Cite
|
Sign up to set email alerts
|

Three Siblings with Prader-Willi Syndrome: Brief Review of Sleep and Prader-Willi Syndrome

Abstract: Prader-Willi syndrome (PWS) is a genetic disorder characterized by short stature, mental retardation, hypotonia, functionally deficient gonads, and uncontrolled appetite leading to extreme obesity at an early age. Patients with this condition require multidisciplinary medical care, which facilitates a significant improvement in quality of life. PWS is the first human disorder to be attributed to genomic imprinting. Prevalence varies in the literature, ranging from 1 in 8,000 in the Swedish population to 1 in 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Short stature, hypogonadism, hypotonia, and cognitive/behavior problems are common features. The incidence is one in 10,000–30,000 with most cases due to sporadic events; however, 13 familial cases of PWS have been reported (Bingeliene, Shapiro, & Chung, 2015; Burke, Kousseff, Gleeson, O’Connell, & Delvin, 1987; Buiting et al, 2000; Clarren & Smith, 1977; Ishikawa, Kanayama, & Wada, 1987; Ishikawa, Kibe, & Wada, 1996; Jancar, 1971; Lubinsky et al., 1987; McEntagart, Webb, Hardy, & King, 2000; Ming et al, 2000; Ohta et al, 1999; Orstavik et al, 1992; Reis et al, 1994; Teshima et al, 1996). Historically, the first familial cases were reported in 1971 in two affected brothers with PWS, one having a dizygotic twin sister without PWS (Jancar, 1971).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Short stature, hypogonadism, hypotonia, and cognitive/behavior problems are common features. The incidence is one in 10,000–30,000 with most cases due to sporadic events; however, 13 familial cases of PWS have been reported (Bingeliene, Shapiro, & Chung, 2015; Burke, Kousseff, Gleeson, O’Connell, & Delvin, 1987; Buiting et al, 2000; Clarren & Smith, 1977; Ishikawa, Kanayama, & Wada, 1987; Ishikawa, Kibe, & Wada, 1996; Jancar, 1971; Lubinsky et al., 1987; McEntagart, Webb, Hardy, & King, 2000; Ming et al, 2000; Ohta et al, 1999; Orstavik et al, 1992; Reis et al, 1994; Teshima et al, 1996). Historically, the first familial cases were reported in 1971 in two affected brothers with PWS, one having a dizygotic twin sister without PWS (Jancar, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…The minor criteria are decreased fetal movement, characteristic behavioral problems (tantrums, obsessive-compulsive behavior), sleep disturbances, short stature, hypopigmentation, small hands and/ or feet, eye abnormalities, thick saliva, speech problems, and skin picking. Ten of the 13 familial cases with PWS in the literature were found to have microdeletions affecting the imprinting center (Bingeliene, Shapiro, & Chung, 2015; Buiting et al, 1995; Buiting et al, 2000; Ishikawa et al, 1987, 1996; McEntagart, Webb, Hardy, & King, 2000; Ming et al, 2000; Ohta et al, 1999; Orstavik et al, 1992; Reis et al, 1994; Teshima et al, 1996). The microdeletions were passed to the subjects from the paternal grandmother through their father.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major criteria list of Prader-Willi syndrome includes neonatal and infantile central hypotonia with poor suck reflex, feeding problems during infancy, excessive weight gain, dysmorphic face features which involves narrow face and almond shape eyes, hypogonadism, hyperphagia, global developmental delay and mental retardation. Also could be minor criteria: decreased fetal activity, behavior problems, speech articulation defects, sleep disturbance, thick viscous saliva and other individual indications (GUNAY-AYGUN et al, 2001;BINGELIENE et al, 2015). LANDAU et al (2016) reported case about 3 weeks newborn with typical neonatal characteristics such as severe hypotonia, poor feeding, inability to suck, dysmorphic features and cryptorchidism.…”
Section: Discussionmentioning
confidence: 99%